Polymorphisms in the GHRL gene and their associations with traits of economic interest in beef cattle - Braz, C. U. [UNESP]; Camargo, G. M. F. [UNESP]; Cardoso, D. F. [UNESP]; Gil, F. M. M. [UNESP]; Fonseca, P. D. S. [UNESP]; Cyrillo, J. N. S. G.; Mercadante, M. E. Z.; Oliveira, H. N. [UNESP]; Tonhati, H. [UNESP] (Funpec-editora, 2015)
The hormone ghrelin is produced in the stomach wall, has an orexigenic function, stimulates growth hormone secretion, and affects the energy balance of the animal. Therefore, the ghrelin gene (GHRL) is considered to be a good candidate marker for the identification of traits of great economic importance in cattle, such as those associated with feed intake, growth, and carcass quality. The use of molecular genetic markers associated with such traits permits the earlier and more accurate identification of superior animals, thus reducing the interval between generations, and increasing the genetic gain. Six SNPs were found in the GHRL gene, located in intron 3, intron 4, and exon 5. The positions of the SNPs on the gene and the substitutions were: g.2184A>G, g.2347T>C, g.4469T>C, g.4548A>G, g.4663T>C, and g.4729T>C (GenBank accession No. JX565585). After analysis of linkage disequilibrium, association tests were performed between four SNPs with the traits year weight for males, yearling weight for females, dry matter intake, loin eye area, and rump fat thickness (P <= 0.05). Therefore, GHRL is an important candidate gene that may be used to identify genetic variations that influence traits of economic importance in beef cattle.
Keywords: GHRL; Molecular markers; Nellore; SNP